Influence of the structure and phase composition of the bond interface on aluminium–copper lap welds strength. (17th February 2018) - Andrade, D. G.; Galvão, I.; Verdera, D.; Leitão, C.; Rodrigues, D. M.
ABSTRACT: The structure and phase composition of the bond interface of aluminium–copper lap welds produced by friction stir welding and tool-assisted friction welding were analysed. Microstructural analysis proved that no through-interface material flow took place in tool-assisted friction welding and that aluminium–copper joining resulted from the formation of a thin and continuous intermetallic layer at the lap interface. For the welds produced by friction stir welding, evidences of through-interface material flow were found, promoting mechanical interlocking of both base materials, at the lap interface, and formation of discontinuous intermetallic layers. Mechanical testing showed that the tool-assisted friction welds, with excellent surface finishing, had low strength, contrary to the friction stir welds, which displayed excellent bond strength. The comparison of the mechanical and microstructural results, for both weld types, pointed to the ineffectiveness of the continuous intermetallic layer in providing high strength bonding.